State policy in the field of circulation of precious metals and stones in the first years of soviet power as a critical factor in the development of the national economy in the 1920s. (based on the example of the South of Russia) - E. N. Badmaeva; K. B. Monakhova (Nomadic Civilization: Historical Research, 2024)
The modernization processes in economic policy that took place in the early years in Soviet Russia significantly influenced the gold mining situation, including in the field of circulation of precious metals and precious stones, which was in a depressed state. In the presented scientific publication, the authors examine the state policy of the state in relation to precious metals and precious stones as the most important factor in solving economic problems in the early 1920s. Based on generally accepted international requirements and standards for gold currencies, their integral role in the global monetary system is assessed. This is, first of all, monetary circulation; financial interaction with foreign countries and settlements with them; loan guarantees and repayment of external debt, as well as the formation of a mobilization foreign exchange reserve. Using the example of the territories of the South of Russia, including the nomadic Kalmyk people, it is shown in detail that the Soviet state, as a result of extreme measures — voluntaryforced confiscation of precious metals and stones, managed to contribute to the fight against the famine disaster and at the same time replenish the state treasury. It has been proven that by 1923 the external foreign currency debt and budget deficit had decreased; the country’s gold reserves began to increase; a single center for the management and circulation of precious metals and precious stones was created